2013
DOI: 10.3402/fnr.v57i0.20823
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding, introduction of other foods and effects on health: a systematic literature review for the 5th Nordic Nutrition Recommendations

Abstract: The present systematic literature review is part of the 5th revision of the Nordic Nutrition Recommendations. The overall aim was to review recent scientific data valid in a Nordic setting on the short- and long-term health effects of breastfeeding (duration of both any and exclusive breastfeeding) and introduction of foods other than breast milk. The initial literature search resulted in 2,011 abstracts; 416 identified as potentially relevant. Full paper review resulted in 60 quality assessed papers (6A, 48B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
0
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 79 publications
(168 reference statements)
9
140
0
10
Order By: Relevance
“…In fact, the longer a child remains an only child, the stronger the association with overweight. As previously reported by our group, among older singletons the association with overweight (OR 1·70, 95 % CI 1·44, 2·01) was greater than for younger singletons (OR 1·32, 95 % CI 1·10, 1·60) (32) . The potential behavioural mediators examined (playtime outdoors, screen time/d, propensity to consume sugar or fat, parental attitudes towards food rewards and television in the child's bedroom) did not attenuate the relationship between only children and overweight with associated OR ranging from 1·51 to 1·58 when each mediator was explored individually and in combination.…”
Section: Family Structure and Overweightsupporting
confidence: 86%
“…In fact, the longer a child remains an only child, the stronger the association with overweight. As previously reported by our group, among older singletons the association with overweight (OR 1·70, 95 % CI 1·44, 2·01) was greater than for younger singletons (OR 1·32, 95 % CI 1·10, 1·60) (32) . The potential behavioural mediators examined (playtime outdoors, screen time/d, propensity to consume sugar or fat, parental attitudes towards food rewards and television in the child's bedroom) did not attenuate the relationship between only children and overweight with associated OR ranging from 1·51 to 1·58 when each mediator was explored individually and in combination.…”
Section: Family Structure and Overweightsupporting
confidence: 86%
“…Comparative studies in affluent countries have indicated important health advantages of breast-feeding over formula-feeding for the recipient infants, such as lower incidence of gastrointestinal and respiratory tract infections (Ip et al, 2007;Agostoni et al, 2009;Hörnell et al, 2013b) and of otitis media (Hörnell et al, 2013b) and a lower risk of overweight and obesity (von Kries et al, 1999;Toschke et al, 2002;Owen et al, 2005;Hörnell et al, 2013b).…”
Section: Terms Of Reference As Provided By the European Commissionmentioning
confidence: 99%
“…Breast-feeding also aims to build the emotional and biological relationship between mother and the baby [1][2][3][4][5][6][7]. Young mothers having little experiences are commonly confused about the duration and initiation in breast-feeding.…”
Section: Introductionmentioning
confidence: 99%